2021
DOI: 10.11613/bm.2021.020706
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 infection among children in Children’s Hospital Zagreb during the initial and second wave of COVID-19 pandemic in Croatia

Abstract: Introduction:The study aimed to investigate the prevalence and titres of anti-SARS-CoV-2 antibodies in children treated at the Children's Hospital Zagreb in the first and the second wave of the COVID-19 pandemic. Statistical significance of difference at two time points was done to determine how restrictive epidemiological measures and exposure of children to COVID-19 infection affect this prevalence in different age groups. Materials and methods: At the first time point (13th to 29th May 2020), 240 samples an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…European countries with elderly demographics were severely hit [8], especially during periods of exponential increase, also denominated pandemic "waves". In Croatia, a second and a third wave were identified from October 2020 to December 2020, and from February 2021 to May 2021, respectively [9,10]. These waves were associated with increased mortality and healthcare burden, with a peak in intensive care unit (ICU) admissions associated to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…European countries with elderly demographics were severely hit [8], especially during periods of exponential increase, also denominated pandemic "waves". In Croatia, a second and a third wave were identified from October 2020 to December 2020, and from February 2021 to May 2021, respectively [9,10]. These waves were associated with increased mortality and healthcare burden, with a peak in intensive care unit (ICU) admissions associated to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Children and adolescents were tested at three time points: May 2020 (first wave), October-November 2020 (peak of the second wave) and December 2020-February 2021 (end of the second wave). The VNT seroprevalence rate in the pediatric population differed with 2.9%, 8.4% and 19.0% seropositive participants [14,17]. While there was no difference in the seropositivity after the first wave, this population group showed a lower prevalence rate compared to the general adult population after the second wave [17].…”
Section: Covid-19 In Humansmentioning
confidence: 79%
“…A more recent study conducted among children from Children's hospital Zagreb showed that the prevalence of anti-SARS-CoV-2 antibodies differed significantly between the first wave (2.9%) and the second wave (8.4%) of the COVID-19 pandemic (7).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, 2.2% of the general population were shown to be ELISA positive after the first wave, with low titers of NT antibodies detected in only 0.2% of individuals ( 6 ). A more recent study conducted among children from Children’s hospital Zagreb showed that the prevalence of anti-SARS-CoV-2 antibodies differed significantly between the first wave (2.9%) and the second wave (8.4%) of the COVID-19 pandemic ( 7 ).…”
Section: Discussionmentioning
confidence: 99%